(untitled) (Czech Journal of International Relations, 2021)
This volume offers a profoundly new interpretation of the impact of modern diasporas on democracy, challenging the orthodox understanding that ties these two concepts to a bounded form of territory. Considering democracy and diaspora through a deterritorialised lens, it takes the post-Euromaidan Ukraine as a central case study to show how modern diasporas are actively involved in shaping democracy from a distance, and through their political activity are becoming increasingly democratised themselves. An examination of how power-sharing democracies function beyond the territorial state, Democracy, Diaspora, Territory: Europe and Cross Border Politics compels us to reassess what we mean by democracy and diaspora today, and why we need to focus on the deterritorialised dimensions of these phenomena if we are to adequately address the crises confronting numerous democracies. As such, it will appeal to scholars of sociology and politics with interests in migration and diaspora, political theory, citizenship and democracy.